The painted girls [large type] - Buchanan, Cathy Marie (Wheeler Publishing, 2013)
In belle époque Paris, the Van Goethem sisters struggle for survival after the sudden death of their father, a situation that prompts young Marie's ballet training and her introduction to a genius painter.